Migrants’ Experiences With Limited Access to Social Protection in a Framework of EU Post‐National Policies - Scheibelhofer, Elisabeth (2022)
It has been argued that nation‐states confront migrant protection with a highly diverse array of measures ranging from excluding strategies (often labelled as “welfare chauvinism”) to more inclusionary, post‐national approaches. While exclusionary strategies are often guided by nativist principles such as citizenship, post‐national approaches of social protection are usually based on residence. Building on an international comparative project with a focus on free movement within the European Union, and involving four pairs of EU member states, this article argues that the extremes of these two ways of understanding nation‐state approaches to migrant social protection are not mutually exclusive, as has been discussed so far, but, instead, are intertwined with one another. While there is a common (and globally unique) framework on the EU level for the coordination of mobile citizens’ social protection, EU member states determine their strategies using residence as a main tool to govern intra‐EU migration. We differentiate between three main intertwining strategies applied by nation‐states in this respect: generally, selectively, and purposefully gated access to social protection. All three potentially lead to the social exclusion of migrants, particularly those who cannot prove their residence status in line with institutional regulations due to their undocumented living situations or their transnational lifestyles.